Financial Knowledge and Risky Investment Behaviour: Insights from Nepalese Stock Market Investors - Rana, Surya Bahadur; Gautam, Rishi Raj (Journal of Business and Social Sciences Research, 2025)
This study examines the influence of individual factors, such as risk aversion and locus of control, on risky investment behaviour. Additionally, it explores whether financial knowledge plays a moderating role in the relationship between these factors and risky investment behaviour. Based on a survey of 386 participants from the stock market of Nepal conducted during August and September of 2024, and using hierarchical regression to test the proposed hypotheses, the findings revealed that risk aversion has a significant negative effect on risky investment behaviour, while locus of control showed no evidence of being a predictor of risky investment behaviour. Finally, the study demonstrated that financial knowledge moderated these relationships, altering the dynamics between risk aversion, locus of control, and risky investment behaviour. The study’s findings suggest that enhancing financial knowledge can mitigate the negative effects of risk aversion and strengthen investment decision-making, while also highlighting the limited role of locus of control in predicting risky investment behaviour. The main implication of the study finding is that higher financial knowledge encourages individuals with an external locus of control to assume greater personal responsibility when making risky financial decisions. These insights hold particular importance for policymakers and financial intermediaries, highlighting how improved financial knowledge can shape investment attitudes and risk-taking behaviours.